MONITORING AND CONTROL DESIGN USING INTERNET OF THINGS BASED MICROCONTROLLER - Indra Ava Dianta; Danang, Danang; Ahmad Ashifuddin Aqham; Budi Hartono; Amad Maijun (UNIVERSITAS STEKOM, 2023)
Technology has the potential to be employed within the realm of electronics and informatics, particularly for the purpose of securing household doors using a smartphone through an internet connection. The Internet of Things (IoT) embodies a concept where internet-enabled devices can communicate with each other and their surrounding objects. This endeavor seeks to create a prototype using key components, including NodeMCU Esp8266, Servo Motor, and Fingerprint Module, with the ultimate goal of simplifying daily tasks and alleviating concerns about leaving the door unlocked upon leaving the house. The mechanism of this device entails utilizing a smartphone app to establish an internet connection, enabling users to seamlessly close and lock their house door. The underlying intention behind developing this tool is to provide assistance in managing both indoor and outdoor activities, addressing the issue of inadvertently leaving the door unlocked, and substituting traditional door locks with fingerprint recognition. By employing this innovation, individuals can conveniently regulate their house door via smartphone, saving time and effort and seamlessly integrating it into their daily routines.